Pengabdian Pembuatan Kontruksi Mesin Pompa Sumur Gali Dan Instalasi Pemipaan Untuk Penyaluran Air Bersih - Simbol Tambing, Frans; Davin Panggabean, Bodian (IAI Darussalam, 2024)
The availability of clean water sources is the main source of problems due to inadequate materials and equipment such as pumps and water distribution pipes. To overcome this problem, well construction was carried out by installing pumps and connecting drainage pipes. Implementation of the service is carried out through several stages which include the preparation stage, construction stage and evaluation stage. The construction of this well is made as simple as possible, namely by connecting a suction pipe from inside the well to the pump, then from the pump a pipe is connected out to the imtak, then from the imtak a pipe is connected to the bathroom which is directly used for daily needs. The equipment used includes a Dab type pump with a power capacity of 450 watts and a water flow produced of around 32 liters/minute, a reservoir with a volume capacity of 1,100 liters in 2 tanks, drainage pipes of the paralon type with sizes 1/2' and 1 /4” plus supporting materials for piping installations such as pipe elbows, pipe glue, water taps and adhesives. The height of the imtak tower is around 2.5 meters above the surface of the dug well, which is made of concrete in the form of a talud. Every time you fill this imtak with water, the water used for daily needs can last ± 2 to 3 days.